2010
DOI: 10.1016/j.cell.2010.06.008
|View full text |Cite
|
Sign up to set email alerts
|

External Lipid PI3P Mediates Entry of Eukaryotic Pathogen Effectors into Plant and Animal Host Cells

Abstract: Pathogens of plants and animals produce effector proteins that are transferred into the cytoplasm of host cells to suppress host defenses. One type of plant pathogens, oomycetes, produces effector proteins with N-terminal RXLR and dEER motifs that enable entry into host cells. We show here that effectors of another pathogen type, fungi, contain functional variants of the RXLR motif, and that the oomycete and fungal RXLR motifs enable binding to the phospholipid, phosphatidylinositol-3-phosphate (PI3P). We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
298
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(304 citation statements)
references
References 47 publications
6
298
0
Order By: Relevance
“…In addition to these, the fungal defensin plectasin from Pseudoplectania nigrella, which shares the same plant defensin CS␣␤ architecture, exhibits growth-inhibitory activity against Gram-positive bacteria through direct binding to the cell wall precursor lipid II (40). It has also been reported that the effector protein from the fungus-like oomycete pathogen binds to outer membrane PI(3)P through a conserved cationic motif to enable entry into host cells (41). Taken together, these observations support the hypothesis that the lipid-binding fungal and plant defensins target a wide range of lipids across different species and that this lipid-targeting mechanism extends back into the early evolution of eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these, the fungal defensin plectasin from Pseudoplectania nigrella, which shares the same plant defensin CS␣␤ architecture, exhibits growth-inhibitory activity against Gram-positive bacteria through direct binding to the cell wall precursor lipid II (40). It has also been reported that the effector protein from the fungus-like oomycete pathogen binds to outer membrane PI(3)P through a conserved cationic motif to enable entry into host cells (41). Taken together, these observations support the hypothesis that the lipid-binding fungal and plant defensins target a wide range of lipids across different species and that this lipid-targeting mechanism extends back into the early evolution of eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Once expressed, this effector passes through the plant secretory system and is secreted into the extracellular space (apoplast); its subsequent reentry into the plant cell can then be traced microscopically via fusion to a fluorescent protein (70). Through the generation of mutations in specific domains suspected to function in delivery of effectors into plant cells and by employing cell reentry assays, it has been possible to identify putative domains required for entry (65,71,72). However, this assay cannot unequivocally demonstrate that when the effector is expressed, it is assuredly secreted into the apoplast prior to reentry.…”
Section: How Are Effectors Deployed In the Host?mentioning
confidence: 99%
“…To examine whether Ras isoforms differentially sort membrane lipids, we used lipid-binding or PH probes to spatially map the distributions of PS (GFP-LactC2) (27,31), phosphatidic acid (PA) (GFP-PH-Spo20) (33), phosphatidylinositol 4,5-bisphosphate (PIP 2 ) (GFP-PH-PLC␦) (34), phosphatidylinositol (3,4,5)-trisphosphate (PIP 3 ) (GFP-PHAkt) (35), phosphatidylinositol 3-phosphate (PI 3 P) (GFP-PH-FYVE) (36), and phosphatidylinositol 4-phosphate (PI 4 P) (GFP-FAPP1) (37) with respect to Ras nanoclusters on intact PMs (Fig. 1a).…”
Section: Ras Nanoclusters Have Different Lipid Compositions But Allmentioning
confidence: 99%